Prediction of Clinical Outcome After Acute Ischemic Stroke: The Value of Repeated Noncontrast Computed Tomography, Computed Tomographic Angiography, and Computed Tomographic Perfusion. Issue 9 (September 2017) - Dankbaar, Jan W.; Horsch, Alexander D.; van den Hoven, Andor F.; Kappelle, L. Jaap; van der Schaaf, Irene C.; van Seeters, Tom; Velthuis, Birgitta K.
Abstract : Background and Purpose—: Early prediction of outcome in acute ischemic stroke is important for clinical management. This study aimed to compare the relationship between early follow-up multimodality computed tomographic (CT) imaging and clinical outcome at 90 days in a large multicenter stroke study. Methods—: From the DUST study (Dutch Acute Stroke Study), patients were selected with (1) anterior circulation occlusion on CT angiography (CTA) and ischemic deficit on CT perfusion (CTP) on admission, and (2) day 3 follow-up noncontrast CT, CTP, and CTA. Follow-up infarct volume on noncontrast CT, poor recanalization on CTA, and poor reperfusion on CTP (mean transit time index ⩽75%) were related to unfavorable outcome after 90 days defined as modified Rankin Scale 3 to 6. Four multivariable models were constructed: (1) only baseline variables (model 1), (2) model 1 with addition of infarct volume, (3) model 1 with addition of recanalization, and (4) model 1 with addition of reperfusion. Area under the curves of the receiver operating characteristic curves of the models were compared using the DeLong test. Results—: A total of 242 patients were included. Poor recanalization was found in 21%, poor reperfusion in 37%, and unfavorable outcome in 44%. The area under the curve of the receiver operating characteristic curve without follow-up imaging was 0.81, with follow-up noncontrast CT 0.85 ( P =0.02), CTA 0.86 ( P =0.01), and CTP 0.86 ( P =0.01). All 3 follow-up imaging modalities improved outcome prediction compared with no imaging. There was no difference between the imaging models. Conclusions—: Follow-up imaging after 3 days improves outcome prediction compared with prediction based on baseline variables alone. CTA recanalization and CTP reperfusion do not outperform noncontrast CT at this time point. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00880113.